CD11b Expression Level Measurement to Distinguish Asthma Phenotype in Pediatric Patients - Tien Budi Febriani; Soeroyo Mahfudz; Emi Azmi Choironi; Ninda Devita; Adika Zhulhi Arjana; Muhammad Nur Imansyah (Avicenna Journal of Medicine)
Background Inflammation is involved in asthma pathogenesis. Based on the majority of inflammatory cells found in blood samples, asthma is divided into neutrophilic and eosinophilic phenotype. CD11b is a leukocyte surface antigen that is involved in the inflammation process. However, the immunologic response mechanism in asthma phenotypes, especially in pediatric population, is still unclear. The aim of this study was to find the difference of CD11b expression in neutrophilic and eosinophilic phenotype of asthma in pediatric patients.